(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
Research goal – information of floristically rich and hight – productive agrocenosis for the production of qualitative forage. Long – term field experiments were established on two types of soils using species of grasses with biological and economic traits different from forage legume and grass families.Persistence, productivity and quality of forage grasses have been determined in mixed swards in different utilization regimes and on different fertilizer backgrounds. It was stated that the rational use of the forage grasses gene fund as well as aperies and varieties of grasses introduced into Latvia can contribute to the formation of night – productive meadows and pastures with the average dry matter (DM) yield 8.5 – 14.0 t ha-1. The produced grasses may he helpful in making top – quality hay and silage which, by their quality parameters (protein, amino acids, mineral substances, ADF and NDF content) are fully corresponding to standards set in high – productive animal feeding.